Salmonella Enteritidis clades in South Africa: why we should be paying more attention - Gallichan, Sarah; Ramalwa, Ntsieni; Thomas, Juno; Feasey, Nicholas; Smith, Anthony M. (Frontiers in Tropical Diseases, 2023)
Salmonella Enteritidis is the most reported non-typhoidal Salmonella serovar and is implicated in both gastroenteritis and invasive non-typhoidal disease. Whole-genome sequence comparison of Salmonella Enteritidis isolates from across the world identified four definitive clades: Outlier, Global Epidemic, East African and West African. Three of these clades were implicated in epidemics: the Global Epidemic clade was linked to poultry-associated gastroenteritis, while the two African clades were related to invasive disease. Despite the recognition of different Salmonella Enteritidis clades, the distribution and epidemiology of these clades across Africa is poorly understood. In our proof-of-concept study, we classified 618 Salmonella Enteritidis isolates originating from four South African provinces over a period of two years (2012 – 2013) into clades using a clade-typing real-time PCR assay. Associations between clades and province of collection, antimicrobial resistance and HIV status were explored using statistical analysis. Majority of the South African isolates were classified within the Outlier clade (61.00%), with fewer classified within the Global Epidemic clade (38.83%) and only one isolate classified within the West African Clade (0.16%). Of note, were the isolates within the Global clade, which were strongly associated with ciprofloxacin resistance (15.42%, OR: 7.45, CI: 3.526 – 15.751) and invasive disease (58.33%, OR: 1.57, CI: 1.13 – 2.17) in humans. The increase in poultry consumption and importation in South Africa has placed the country at risk of a Salmonella Enteritidis epidemic. Thus, there is a necessity for routine monitoring of S. Enteritidis along the farm-to-fork continuum to implement preventative measures.